COMPENSATION FOR LAND PROCUREMENT FOR PUBLIC INTERESTS LAW AND INTERNATIONAL SAFEGUARD PERSPECTIVE - Wibowo, Rimun; Fuad, Fokky; Rifai, Anis (Universitas Labuhanbatu, 2025)
Conflicts when acquiring land for public purposes cannot be avoided. Land acquisition for public purposes is part of development carried out by the state through land acquisition. Conflicts such as land owners not accepting compensation provided by the state include problems during land acquisition. The aim of this research is to find the causes of conflict between land owners and the government when procuring land for public purposes. The second objective is to find a form of compensation that is carried out from the perspective of law and international safeguards. The research method used is a descriptive qualitative method. Meanwhile, data collection was carried out by collecting various scientific articles, laws and international safeguard documents. After that, make comparisons and draw various conclusions. The findings are that there is conflict between the government and land owners because compensation does not match the land owner's perspective. The solution taken is through deliberation to reach a consensus so that the land owner is willing to relinquish their rights to the land. Another result is that the compensation given from a legal perspective is very fair because it takes into account various aspects including the economic value of the land. Meanwhile, SafeGuar International views it as more comprehensive because it is not just compensation based on economic value but there is empowerment for the affected communities, including gender empowerment and replacement of livelihood sources.Keywords: Land Acquisition; Public Interest; International Safeguards; Compensation; Conflict.